HE EXPERIENCE IN APPLICATION OF MOLECULAR GENETIC METHODS FOR INSECTS SPECIES IDENTIFICATION – PREPARING OF SAMPLES TO DNA SEQUENCING - Bragina, T.M.; Bobrenko, M.A.; Rulyova, М.М. (publisher of Kostanay state pedagogical university, 2020)
The article is devoted to the experience of samples preparing for molecular genetic species identification of insects in the framework of some international projects carried out in Kostanay State Pedagogical University named after U. Sultangazin. Individuals of different Coleoptera families collected in territory of the Kostanay region were an object of this research. DNA-barcoding methods were used for invertebrates of Kostanay region for the first time.
Keywords: DNA-barcoding; gel-electrophoresis; insects; molecular genetic methods; PCR machine